VISION OF SERVICE AND NECESSITY OF SERVICEOLOGY (Proceedings of the YSU C: Geological and Geographical Sciences, 2015)
In the article the following stereotypes related to category Service have been drawn up and discussed: service as a third sector of labour division, service as an indicator of globalization, service society, service state, service human. All of these represent service as a system of services and type of activities based on theoreticalmethodological diversity. The object of serviceology is the human’s non-material needs and the effectiveness of human material needs satisfaction. The aspect to study serviceology is the educational scientific system which creates service human, service state and formation of state. The science of service tries to systematize all spheres of social life and makes possibilities for scientific solutions of actual diverse problems based on theory and methodology of effectiveness of human needs satisfaction.
Keywords: services; service human; service society; service state; serviceology